Clinical care and complicity with torture. (2nd February 2018) - Berger, Zackary; Rubenstein, Leonard S; DeCamp, Matthew
Abstract : In the light of US Central Intelligence Agency guidelines that limited routine care of detainees to promote torture, Zackary Berger and colleagues call for sanctions against health professionals who cooperate